(untitled) (Journal of Nepal Physical Society, 2024)
Multimedia communication refers to more than one medium of communication. For example, if we consider a textbook, it has some text at a minimum. It may also have pictures, graphs, tables of data, and so on. In the modern era of digital technology, its span has widened to audio and video recordings and interactive animations. This paper investigates the effectiveness of interactive multimedia tools in improving student learning of physics concepts in introductory college courses. We implemented interactive multimedia tools in the studio-style and Student-Centered Active Learning Environment for Undergraduate Programs (SCALE-UP) classroom settings, and studied their impact on student learning of physics concepts through surveys on their perceptions related to the learning activities based on those tools. Our analysis of the survey data shows that the majority of the students who participated in the surveys found the interactive multimedia activities helpful for learning physics concepts.